Evaluating care pathways for community psychiatry in England: a qualitative study. Issue 2 (23rd February 2012) - Khandaker, Golam M.; Gandamaneni, Praveen K.; Dibben, Claire R. M.; Cherukuru, Srinivasarao; Cairns, Paul; Ray, Manaan K.
Abstract: Objectives In view of forthcoming 'payment by results' (PbR) for mental health, increasing number of National Health Service (NHS) Trusts are reorganizing their community services for working age adults to create care pathways. However, research base for the care pathways model in mental health is limited. Our NHS Foundation Trust was one of the first to introduce care pathways for community psychiatry in the UK. We have carried out a qualitative study to evaluate how this model works out in practice, including its impact on quality of patient care, mental health professionals and primary care. Methods We interviewed doctors, multidisciplinary staff and Trusts managers (19 in total). Transcripts of recorded interviews were coded and analysed thematically using a grounded theory approach. Results Overall, despite teething problems, working in pathways was generally seen as a positive change. It led to more focused interventions being offered, and practitioners being held to account over clear standards of care. It is more cost‐effective and allows for active case management and clear clinical leadership. It is recovery focused and encourages social inclusion. The arbitrary time frame, strict criteria and thresholds for different teams can create issues. Improved communication, flexible and patient‐centred approach, staff supervision, and increasing support to primary care were felt to be central to this model working efficiently and effectively. Conclusions Introduction of care pathways is an important step towards effective implementation of PbR for mental health. Our study would inform future research into care pathways, facilitate organizational learning and help to improve effectiveness of services.